2017
DOI: 10.1111/ijfs.13711
|View full text |Cite
|
Sign up to set email alerts
|

Reductionin Listeria monocytogenes, Salmonella enterica and Escherichia coli O157:H7 in vitro and on tomato by sophorolipid and sanitiser as affected by temperature and storage time

Abstract: Summary Increased consumption of produce by consumers has been attributed to perceived health benefits of postharvest produce. Pathogen control is crucial because periodic occurrences and contamination of tomato and leafy greens have exacerbated food safety risks for consumers. We investigated the effects of temperatures (5 and 25 °C), storage time (30 min and 24 h) for inactivation of Listeria monocytogenes, Salmonella enterica and Escherichia coli O157:H7 by sophorolipid (SL‐p) produced fermentatively using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
11
1
3
Order By: Relevance
“…Combining lactonic SLs with antimicrobial agents, such as chlorhexidine, sodium lauryl sulfate, tetracycline HCl, and ciprofloxacin, resulted in significant reduction of MIC values against pathogens important for oral hygiene . Olanya et al . reported that combinations of SL and nisin‐based sanitizer showed synergistic effect on E. coli O157:H7, but not L. monocytogenes and S. enterica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining lactonic SLs with antimicrobial agents, such as chlorhexidine, sodium lauryl sulfate, tetracycline HCl, and ciprofloxacin, resulted in significant reduction of MIC values against pathogens important for oral hygiene . Olanya et al . reported that combinations of SL and nisin‐based sanitizer showed synergistic effect on E. coli O157:H7, but not L. monocytogenes and S. enterica .…”
Section: Discussionmentioning
confidence: 99%
“…reported that sophorolipids or SL‐biopolymers inhibited growth of skin pathogen Propionibacterium acnes isolated from salted hides. SLs also affected growth of oral pathogens and food pathogens including Listeria monocytogenes , Salmonella enterica , and Escherichia coli O157:H7 . Because of the excellent surface‐lowering and foam production abilities and antimicrobial activities, SLs have significant applications in various industries and many companies are developing SLs products for food, cosmetics, cleaning, personal care, environmental industries, pharmaceutics, and fungicides…”
Section: Introductionmentioning
confidence: 99%
“…A ação dos soforolipidios também foi estudada por Olanya et al (2018) que reportaram ação antibacteriana do soforolipídio de C. bombicola in vitro em tomate pós colheita, obtendo resultados de inibição de Listeria monocytogenes, Salmonella enterica e Escherichia coli em concentrações a partir de 50 µg.mL -1 . Outros autores investigaram seu efeito em folhas de espinafre contaminadas com Escherichia coli O157:H7, obtendo reduções de 1,4 log UFC/folha logo após tratamento com 1% de soforolipídio e 3.6 log UFC/folha após 7 dias de armazenamento a 4°C Pela Tabela 2, após 30 minutos de exposição na solução de soforolipídios a 4.000 µg.mL -1 eliminou a contaminação de coliformes termotolerantes presente na água de imersão.…”
Section: Soforolipídios Como Sanitizante Aplicados Por Imersão Em Carcaças De Frangounclassified
“…PULATE et al, 2014;ZHANG et al, 2016a)researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs Olanya et al (2018). também reportaram ação antibacteriana do soforolipídio de C. bombicola in vitro e aplicados em tomate pós colheita, obtendo resultados de inibição de Listeria monocytogenes, Salmonella enterica e Escherichia coli em concentrações a partir de 50 mg/L.…”
unclassified